2016
DOI: 10.1038/ngeo2757
|View full text |Cite
|
Sign up to set email alerts
|

An abyssal carbonate compensation depth overshoot in the aftermath of the Palaeocene–Eocene Thermal Maximum

Abstract: The Paleocene-Eocene Thermal Maximum (PETM; ~56 Ma) represents one of the largest and most abrupt greenhouse warming events in Earth history. Marine and terrestrial records document a global >2.5‰ negative carbon isotope excursion (CIE) [1][2][3] coincident with global mean surface ocean warming of >4°C 4 and geochemical and sedimentological evidence for ocean acidification 5,6 . Collectively, these lines of evidence suggest a rapid (10 3 -10 4 years) and massive (~3,000-10,000 PgC) release of 13 C-depleted ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 49 publications
4
82
0
2
Order By: Relevance
“…6g). In combination with decreasing pCO 2 and associated increasing ocean [CO 2− 3 ], the biogenic CaCO 3 production increase drives an overshoot of the LL CCD to depths greater than the pre-event depth, in agreement with theory and sediment core data (Dickens et al, 1997;Leon-Rodriguez and Dickens, 2010;Penman et al, 2016). This overshoot, which is even more pronounced at high latitudes, peaks by 35-45 kyr into the simulation (Fig.…”
Section: Pre-event Steady State and A Long Sample Simulationsupporting
confidence: 70%
“…6g). In combination with decreasing pCO 2 and associated increasing ocean [CO 2− 3 ], the biogenic CaCO 3 production increase drives an overshoot of the LL CCD to depths greater than the pre-event depth, in agreement with theory and sediment core data (Dickens et al, 1997;Leon-Rodriguez and Dickens, 2010;Penman et al, 2016). This overshoot, which is even more pronounced at high latitudes, peaks by 35-45 kyr into the simulation (Fig.…”
Section: Pre-event Steady State and A Long Sample Simulationsupporting
confidence: 70%
“…Short‐ and intermediate‐term effects (kiloyear to tens of kiloyears) involve responses of carbonate saturation and dissolution to changes in atmospheric CO 2 concentrations and related changes in pH and temperature of ocean water. On longer time scales (>100 kyr), changes in weathering rates of silicate and carbonate rocks can buffer and potentially “overshoot” the initial change in carbonate saturation (e.g., Penman et al, ; Walker et al, ; Zeebe et al, ). Both processes can provide positive or negative feedbacks to the primary δ 13 C 0 response to carbon flux perturbations (Table and Figures and ), although the effect would be small due to the similar δ 13 C composition of seawater DIC and of the marine carbonate that contributes to the lithospheric inventory.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Foster et al (2013) found that small benthic foraminifera became more heavily calcified during the PETM, when ocean pH was lower (Penman et al, 2014). By contrast, during the high pH "carbonate overshoot" in the aftermath of the event (Penman et al, 2016), these foraminifera displayed thinner walls . Diverse small benthic foraminifera assemblages have also been found living in highly undersaturated oligohaline conditions (Flako-Zaritsky et al, 2011).…”
Section: Towards Understanding the Differential Response Of Foraminifmentioning
confidence: 99%